Does Exposure to Foreign Culture Influence Creativity? Maybe It's Not Only Due to Concept Expansion - Tan, Liu; Wang, Xiaoqin; Guo, Chanyu; Zeng, Rongcan; Zhou, Ting; Cao, Guikang (Frontiers in Psychology, 2019)
Multicultural experience refers to those experiences gained through individuals’ contact with other cultures. This study focused on exploring whether knowledge of different cultures can improve creative performance-and also how multicultural experiences influenced this performance through changes in individual’s physiological mechanisms. Experiment 1 explored the influence of different cultural primings on creative story-writing tasks. 89 Chinese college students were randomly assigned to 4 conditions: sole American culture, dual cultures, sole Chinese culture or control condition, and made to watch 45-minute slides with cultural elements—including pictures, music and videos,—and then they were asked to complete the creative story-writing task. The results showed that American cultrue priming group’s score was significantly higher than the control condition with regards to the uniqueness and novelty of the creative story-writing task. Experiment 2 was aimed at exploring the relationship between physiological arousal levels induced by different cultural and creative performance. We divided the whole experiment into five stages,—including the baseline, picture, listening to music, watching video and completing creative tasks. Through Biofeedback measurement, we recorded the physiological indexes of participants in different groups in every stage, including skin conductance, thermal, electroencephalographic and heart rate. The results showed that contact with foreign cultures would increase individuals' physiological arousal level and brain activity, which contributed to the following creative task.